Effect of different intraoperative blood pressure regulation levels on postoperative myocardial injury in patients undergoing radical mastectomy for breast cancer after receiving neoadjuvant chemotherapy: a study protocol for a randomised controlled trial - Ying Zhang; Zhou Zhou; Xinxin Wang; Xiaobao Zhang; Hongya Liu; Xiaoqiao Sang; Yingge Liu (BMJ Open)
Introduction For patients with breast cancer receiving preoperative neoadjuvant chemotherapy with anthracyclines, there is an increased risk of postoperative myocardial injury due to the cardiotoxicity of the chemotherapeutic agents. The optimal intraoperative blood pressure regulation regimen for these patients is unclear. This study is being conducted to determine whether targeting mean arterial pressure (MAP) to 100%–120% of the patient’s baseline blood pressure reduces the incidence of myocardial injury after non-cardiac surgery (MINS) compared with targeting MAP to 80%–100%. MINS is defined as elevated cardiac troponin levels within 30 days after non-cardiac surgery with or without clinical and electrocardiographic signs of cardiac ischaemia.Methods and analysis The study is a single-centre, single-blind, prospective randomised controlled trial. It is expected to enrol 166 subjects receiving neoadjuvant chemotherapy with anthracyclines, between the ages of 40 and 75 years, scheduled for radical mastectomy. Participants will be randomised 1:1 to a lower-level group:intraoperative MAP control at 80%–100% of baseline values or a higher-level group:intraoperative MAP control at 100%–120% of baseline values. The primary outcome is defined by the incidence of MINS at 6–8 hours, 24 hours and 48 hours postoperatively. The secondary outcomes are heart-type free fatty acid-binding protein values at 1–2 hours, 6–8 hours and 24 hours postoperatively; the incidence of acute kidney injury within 48 hours postoperatively; the Quality of Recovery-15 score at 24 hours, 48 hours postoperatively; post-anaesthesia care unit length of stay; other postoperative cardiovascular complications; the number of times rescue analgesia and antiemetics are required; the time to first ambulation and length of postoperative hospitalisation.Ethics and dissemination This study involves the participation of human subjects and has received approval from the Clinical Trial Ethics Committee at The Affiliated Lianyungang Hospital of Xuzhou Medical University (approval number: KY-20230915001). Study results will be presented at scientific meetings and in scientific publications.Trial registration number ChiCTR2300077675.